Middle school curriculum, instruction, and assessment - Anfara, Vincent A.; Stacki, Sandra L. (Handbook of research in middle level education series., 2002)
This handbook explores the curriculum, instruction and assessment used in middle schools. The essays cover: curriculum integration - history and research; the relationship between middle grades teacher certification and teaching practices; and cohorts in middle level teacher preparation.